2018
DOI: 10.1186/s13613-018-0401-y
|View full text |Cite
|
Sign up to set email alerts
|

Diaphragm function and weaning from mechanical ventilation: an ultrasound and phrenic nerve stimulation clinical study

Abstract: BackgroundDiaphragm dysfunction is defined by a value of twitch tracheal pressure in response to magnetic phrenic stimulation (twitch pressure) amounting to less than 11 cmH2O. This study assessed whether this threshold or a lower one would predict accurately weaning failure from mechanical ventilation. Twitch pressure was compared to ultrasound measurement of diaphragm function.MethodsIn patients undergoing a first spontaneous breathing trial, diaphragm function was evaluated by twitch pressure and by diaphra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
0
10

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(89 citation statements)
references
References 35 publications
1
74
0
10
Order By: Relevance
“…Informed consent was obtained from all patients or their relatives. Some data from this cohort have already been published elsewhere [13,18,19].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Informed consent was obtained from all patients or their relatives. Some data from this cohort have already been published elsewhere [13,18,19].…”
Section: Methodsmentioning
confidence: 99%
“…Diaphragm function was assessed by the change in tracheal pressure in response to magnetic stimulation (Ptr,stim), as described previously [13] and limb muscle strength was assessed by the Medical Research Council (MRC) score in patients screened for level of consciousness and understanding [2,21]. Patients with a Ptr,stim less than 11 cm H 2 O were considered to have diaphragm dysfunction and patients with a Ptr,stim less than 7 cmH 2 O were considered to have severe diaphragm dysfunction [18]. Patients with an MRC score less than 48 were considered to have ICU-AW [2].…”
Section: Initial Study Populationmentioning
confidence: 99%
“…We have no histological data on patients' diaphragms, and further studies, maybe involving muscular structure evaluation, are needed to judge if the muscle actually benefits from the assisted activity, even if in some cases, this might not translate in improved outcome due to the co-existence of too many confounding factors in an ICU patient. Regarding diaphragm activity, some studies report that the level of TFdi can be used as a predictor of successful weaning [9,30,31]. This evidence was not confirmed in other studies.…”
Section: Discussionmentioning
confidence: 80%
“…The targets of this type of ventilation would be to avoid excessive or minimal diaphragm activity, trying to mimic the inspiratory effort of healthy subjects [8]. In fact, a diaphragmatic thickening fraction between 25 and 40% (considered the reference range for resting tidal breathing) was associated with stable diaphragmatic thickness [2], shorter duration of mechanical ventilation [1], and higher incidence of weaning success [9]. Given all of these, it is advisable to strictly monitor patients' inspiratory efforts, and specifically diaphragmatic function, while avoiding lung injury [10].…”
Section: Introductionmentioning
confidence: 99%
“…Far from being merely an inconvenient side effect of mechanical ventilation, respiratory muscle weakness can directly affect a patient's ventilation and ICU outcomes. Recent ultrasound studies of diaphragm thickness (a surrogate measure of inspiratory muscle strength) revealed that by day 4 of mechanical ventilation, reduced diaphragm thickness could be detected in 41% of patients [4,10]. Reduced diaphragm thickness is associated with reduced likelihood of weaning from mechanical ventilation, higher likelihood of complications, and prolonged ICU admission [4].…”
Section: Respiratory Muscle Weakness In Icu Patients: a Call To Actionmentioning
confidence: 99%